The Role of Blood Biomarker p-tau217 in the Early Detection of Alzheimer's Disease: A Systematic Review - Mangde Anata Sindhu (Health & Medical Sciences, 2026)
This systematic review sought to assess the function of the blood biomarker phosphorylated tau 217 (p-tau217) in the early identification of Alzheimer's disease. A systematic review was carried out adhering to the PRISMA 2020 protocols. Literature searches were executed in PubMed, ScienceDirect, and Scopus to locate original studies published between 2023 and 2026. Eligible studies assessed blood p-tau217 in individuals with mild cognitive impairment, suspected Alzheimer's disease, Alzheimer's disease, or at-risk populations and reported diagnostic performance or correlations with established Alzheimer's biomarkers. Study quality was evaluated utilizing QUADAS-2 for diagnostic accuracy studies and the Study Quality Assessment Tools for observational and longitudinal studies. A total of 328 records were retrieved, of which 18 studies met the inclusion criteria. Research consistently demonstrates that plasma p-tau217 serves as a highly accurate biomarker for identifying the biological pathology of Alzheimer's disease, specifically regarding amyloid and tau status. Numerous studies have reported impressive area under the curve (AUC) scores between 0.92 and 0.97. When p-tau217 is paired with Aβ42 or the Aβ42/40 ratio, its diagnostic precision improves significantly, particularly in patients who are cognitively normal or in the preclinical stages of the disease.